World Economic Outlook, May 1991. (World Economic Outlook; World Economic Outlook ;, 1991)
This paper highlights that world economic growth is estimated to have declined from 3u percent in 1989 to 2 percent in 1990, reflecting a slowdown in the industrial countries and a fall in economic activity in developing countries of Eastern Europe, the Middle East, and the Western Hemisphere. The growth of the world economy is expected to decline further in 1991 (to 1u percent) owing to the weakness of some industrial economies, and to further declines in output in the Middle East and in Eastern Europe.